2021
DOI: 10.11159/jbeb.2020.004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of a Phenomenological Thrombosis Model and Growth Rate Characterisation

Abstract: Aortic dissection is a severe cardiovascular disease caused by the occurrence of a tear in the aortic wall. As a result, the blood penetrates the wall and makes a new blood channel called the false lumen. The haemodynamic conditions in the false lumen may contribute to the formation of thrombi, which influence the patient's diagnosis and outcomes. In this study, the focus is on a haemodynamic-based model of thrombus formation. Since the model construction entails uncertainties in the model parameters, a varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Six parameters showed significant influence in both quantities of interests considering their first Sobol' indices. This is in line with a recent study conducted by Melito et al 29 in which the authors found that only four of the nine parameters in the model of Menichini 7 were influential for predicting volume fraction of thrombus in a backwards step. However, investigation of parameter interaction via the total Sobol' indices revealed influence of a subset of the nine “non‐influential” parameters according to the first Sobol' indices.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Six parameters showed significant influence in both quantities of interests considering their first Sobol' indices. This is in line with a recent study conducted by Melito et al 29 in which the authors found that only four of the nine parameters in the model of Menichini 7 were influential for predicting volume fraction of thrombus in a backwards step. However, investigation of parameter interaction via the total Sobol' indices revealed influence of a subset of the nine “non‐influential” parameters according to the first Sobol' indices.…”
Section: Discussionsupporting
confidence: 91%
“…Previous investigators have introduced several uncertainty quantification (UQ) strategies to evaluate the effect of such uncertainties on model performance in the context of blood flows 22–25 . UQ analyses in thrombosis models have been performed to identify the sensitivity of input parameters 26–29 . In most sensitivity studies, the global Morris method 30 or the Sobol' indices method 31 have been used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the complexity of the model and make it more efficient, it is beneficial to reduce the number of equations and variables. Melito et al (2020) performed a sensitivity analysis on Menichini and Xu’s 2016 model and showed that not all the model parameters influence thrombus formation, meaning that the model can be reduced. Model reduction is of interest for several reasons.…”
Section: Introductionmentioning
confidence: 99%